The automation of the CommGroup Training Library - Salas, Jody C. (Institute of Library Science, University of the Philippines Diliman, 2001)
The Communication Group Training is responsible for giving skill training and other seminars, both technical and non-technical to the Lopez Group of Companies, composing of BayanTel, ABS-CBN and Sky Cable. On the average, they conduct daily training to more than fifty employees. Thus, it is valuable for them to have fast access to training materials especially during preparation for a scheduled training. The CommGroup Training Library supports the curricular and instructional programs of the department. The library boasts of an extensive collection of print materials including books, periodicals, training materials and multi-media sources like videotapes.